Protective Effect of a Water-Soluble Carotenoid-Rich Extract of Cordyceps militaris against Light-Evoked Functional Vision Deterioration in Mice - Bo-Yie Chen (Nutrients, 2022)
Light-evoked retinal photodamage is considered an important factor contributing to functional vision deterioration and can even lead to light maculopathy or dry age-related macular degeneration. Loss of visual acuity (VA) and visual contrast sensitivity function (VCSF) are the major symptoms of retinal degenerative diseases. Cordyceps militaris is a carotenoid-rich Chinese medicinal fungus with antioxidant, anti-inflammatory, and immunomodulatory functions. C. militaris extract is a natural substance, and its bioactive constituents have been shown to confer health benefits, but their application in retinal tissue and functional vision protection in vivo remain incompletely understood. In the present study, we evaluated the influence of water-soluble, carotenoid-rich C. militaris extracts on the visual performance of light-damaged mouse retinas in vivo, using adult female CD-1® (ICR) albino mice. We showed that oral administration of this C. militaris extract (10 mg/kg, twice daily) protected the neural retina tissue against light-evoked photoreceptor cell death, reduced Müller cell hypertrophic gliosis, and elevated GSH levels and promoted the recovery of VA- and VCSF-thresholds, especially for high spatial frequency-characterized vision. These results suggest that, probably because of its water-soluble carotenoids, C. militaris extract has the potential to prevent or treat light-induced visual dysfunction.